José de San Martín and the indigenous political space. Department of Lima, 1821-1822 - Guarisco, Claudia (2023)
The piece is about the changes introduced by José de San Martín in the local political organization of the Intendancy of Lima, between 1821 and 1822. Those institutional changes had two sources: Spanish Liberalism and the so-called Absolute Monarchy. This work also explores the impact of San Martín’s presence among indigenous towns.